The skills of contemplative thinking included in the books of life sciences for the ninth and tenth grades of the basic stage in Jordan - Al- Maaytah, Hiam Mohammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed at revealing the degree of inclusion of the thinking skills in the books of life sciences in Jordan by analyzing the content of these books in order to answer the study questions. The study used the descriptive method. The tool consisted in building a list of thinking skills, The results of the study revealed the availability of cognitive thinking skills to varying degrees in the books of life sciences (ninth and tenth) in Jordan, where the skill (visual vision), a high percentage , And came skilled Other low rates respectively (give convincing explanations, to reach conclusions, disclosure of inaccuracies, the proposed solutions). The results showed that the book of life sciences for the tenth grade was ranked first in the total number of repetitions (352), with the tenth grade (193) repeated, followed by the ninth grade book (159) To conduct further studies to identify the skills of contemplative thinking in books and other stages of study.
Keywords: Thinking skills; Life Sciences; Content Analysis